Thermal aging effects on microstructures and mechanical properties of an environmentally friendly eutectic tin-copper solder alloy - Gain, A.; Zhang, L.; Quadir, Md Zakaria (Elsevier, 2016)
This paper describes the changes in microstructures and their effects on property degradations in an environmentally friendly eutectic [Formula presented].7Cu (wt.%) solder alloy when subjected to harsh service conditions. A thorough microscopy investigation was conducted by scanning electron microscopy (SEM), electron backscattered diffraction (EBSD) and diffraction analysis with transmission electron microscopy (TEM). In the as-received alloy Cu6Sn5 intermetallic compound (IMC) particles are dispersed in the grain interiors and grain boundaries of ß-Sn matrix. When the alloy was exposed for 60 days at 150 °C, the size of Cu6Sn5 IMC particles and Sn matrix grains were increased significantly. As a result the mechanical reliability of electronic interconnections turned inferior. This was confirmed by measuring a range of electrical and mechanical properties that include electrical resistivity, Young's moduli, shear moduli, microhardness and nano indentation creep behaviour. A comparison between the as-received and age-treated alloy shows that the degradation in Young's and shear moduli was about 10.6 and 9.9%, respectively, and that in hardness was about 25%. However the age treatment improved the damping property of the alloy.